Study of Local People Perception Related to Landslide Hazard: A Case of Tawangmangu Sub-District Karanganyar Regency Indonesia - Heru Setiawan; Dyah R Hizbaron (Universitas Muhammadiyah Surakarta, 2014)
In 2007, a series of landslides occurred at Tawangmangu, resulting in the collapse of several houses and the death of dozens of people. One essential pathway to reduce the vulnerability of communities goes through an increased preparedness. The present contribution aims to determine existing level of preparedness by analysing the people perception and knowledgeof landslides. Survey method with random sampling technique was applied to assess the level of people perception and to analysis local people knowledge regarding with landslide. The number of respondents was spread proportionally across five sub-villages; Plalar, Guyon, Sodong, Salere and Ngledoksari. The respondents were interviewed using questionnaires with open and closed questions. Statistical analysis with multiple linear regressions was applied to identify the influencing factors of local people perception related to landside. The result show that people in the area have good knowledge and perception about landslide. This condition is commonly influenced by age and education.